The Effect of Video Intervention on Sensitivity in Early Childhood Teachers - Sappaile, Baso Intang; Kathryn, Morse; Cale, Woolnough (Journal International Inspire Education Technology, 2024)
At this time the world is experiencing rapid developments in science and technology, one of the factors that influences the world of education is an educator, especially early childhood teachers. Therefore, early childhood educators are required to be able to apply video media during learning. Educators in this era pay less attention to empowering learning videos in increasing teacher sensitivity. This research aims to find out how optimal the use of technology is. The method used in this research is quantitative research, data obtained from interviews with research objects. Based on the analysis carried out, research results were found which contained an increase in the effectiveness of early childhood teachers in carrying out the learning process by paying attention to video interventions. The conclusion of this research is that there is an increase in sensitivity by implementing video learning interventions for early childhood teachers. The limitation of this research is that it only focuses on video interventions, whereas there are many other learning media that function as alternatives for teaching and learning in the classroom. The researcher hopes that future researchers can conduct research related to teacher sensitivity using video intervention. This research also recommends that future researchers use the research as a reference in conducting research on video interventions.